Establishing the foundational elements of a public procurement body of knowledge. (December 2018) - McCue, Clifford P; Prier, Eric; Steinfeld, Joshua M
Public procurement scholars have been striving to identify technical and behavioral competencies to drive toward professionalization. However, there is no vetted body of knowledge that practitioners and scholars can use to establish roles and responsibilities. This empirical study outlines a logical process to identify the foundational elements of the body of knowledge, specifically technical competencies, serving as the building blocks for advancement toward a recognized profession. Findings suggest that 87 job tasks can be classified under 6 job domains that contain many of the components and conceptual constructs for the field of public procurement. These domains can improve understanding of the knowledge, skills, and abilities necessary in public administration.